Adaptabilidade e estabilidade de genótipos de cana-de-açúcar nos estados de Goiás e Minas Gerais pelo método GGEbiplot - Souza, Maria Stella Xavier de Araujo (2015)
In recent years, an expansion has been observed in the cultivation of sugarcane in the Brazilian Cerrado. With this, the development of breeding programs aimed at this region has become a very important theme, generating emergency demand for research entities and companies. The objective of this work was to identify sugarcane clones that associate adaptability and stability in the Cerrado region, as well as the more representative locations for selecting and structuring an experimentation network for this region. We used data from experiments installed at locations within the states of Goias and Minas Gerais. Tons of pol per hectare (TPH) and tons of stalk sugarcane per hectare (TSH) were considered. Individual analyses of variance were conducted for each production environment, in addition to the analysis of adaptability and stability by means of the GGE Biplot methodology. It was possible to identify a high productivity, stability and adaptability genotype in at least three of the evaluated locations, with superior significance when compared to the witnesses. The evaluations for TPH trait in the inter-relations of genotype and environment were more discriminating than the TSH trait. We found a higher number of mega-environments for TPH (4) when compared to TSH (2), indicating that the capacity for accumulating sucrose of the genotypes is highly influenced by the environment.